Global research landscape and multisystem health mechanisms of luteolin: a comprehensive bibliometric and network pharmacology study - Guo, Huina; Tian, Xiyan; Wang, Haiyan; Wang, Kexin; Han, Qi; Guo, Yujia; Guan, Xiaoya; Li, Zhongxun; Wen, Xin; Wu, Bohui; Zhao, Liting; Wang, Ying; et al. (Frontiers in Nutrition, 2026)
ObjectiveThis study employs bibliometric and network pharmacology methods to systematically analyze the development trends, knowledge structure, and potential biological mechanisms of luteolin research from 2000 to 2025, providing insights for its application in nutritional health and disease prevention.MethodsBased on the Web of Science Core Collection (WoSCC), combined with Bibliometrix, VOSviewer, and citespace, we conducted analyses of publication characteristics, keywords, journals, and co-citation networks. Simultaneously, integrating TM-MC, string, and Cytoscape, we constructed a luteolin target-pathway-disease network and performed core target and KEGG enrichment analyses.ResultsLuteolin research exhibits sustained growth, with a significant increase after 2021. Research focus has expanded from early antioxidant and anti-inflammatory mechanisms to metabolic health, immune regulation, tumor suppression, and multisystem protection. Network pharmacology identified 239 potential targets, with core targets including TP53, TNF, STAT3, and EGFR, significantly enriched in p53, PI3K–Akt, TNF, and IL-17 pathways. Disease association networks indicate luteolin’s potential to intervene in neurological, circulatory, metabolic, immune, digestive, respiratory disorders, and multiple tumors, exhibiting typical multi-target comprehensive regulatory characteristics.